Real-World Management of Trabectedin/Pegylated Liposomal Doxorubicin in Platinum-Sensitive Recurrent Ovarian Cancer Patients: A National Survey. Issue 6 (July 2017) - Ferrandina, Gabriella; Amadio, Giulia; Paris, Ida; Distefano, Mariagrazia; Palluzzi, Eleonora; de Vincenzo, Rosa; Ricci, Caterina; Scambia, Giovanni
Abstract : Background: Trabectedin (T) plus pegylated liposomal doxorubicin (PLD) is approved for treatment of platinum-sensitive recurrent ovarian cancer (ROC). Despite the recommendations and guidelines, variations in managing T/PLD administration in routine clinical practice cannot be excluded. We aimed at setting up an Italian survey collecting data about management of T/PLD administration in ROC patients. Methods: We carried out the development of a questionnaire-based survey on routine clinical practice in the management of ROC patients administered T/PLD. The survey registered the physicians' approach to modification/discontinuation of treatment, type of modifications, reasons why, and so on. The survey was transmitted to medical oncologists and gynecologic oncologists practicing in national centers/institutions. Results: Fifty-eight Italian centers/institutions returned the compiled questionnaire; participants practiced at community cancer centers or hospitals (56.9%), academic institutions (36.2%), and other settings (private clinics, etc) (6.9%). There was no statistically significant difference in the distribution of practice setting according to geographic areas. Most responders were medical oncologists (84.5%) and were members (82.8%) of at least 1 scientific society or cooperative group. Almost 31.5% of responders reported interruption of the whole treatment, mostly because of toxicity (41.2%), followed by patients' choice (29.4%), or achievement of clinical benefit (23.5%). Dose reduction was referred by 47.4% of responders. Reduction of dose for both drugs was referred by 88.5% of responders, and the extent of dose reduction ranged between 10% and 30%. Conclusions: This survey highlights the gaps in transposing evidence-based or consensus guidelines in the real-world management of T/PLD administration; these findings could be useful in order to focus the attention on specific knowledge and/or experience gaps and plan pertinent educational programs. Abstract : Supplemental digital content is available in the text.